Anti-Müllerian Hormone Levels in Preeclampsia: A Systematic Review of the Literature - Vasilios Pergialiotis; Diamanto Koutaki; Evangelos Christopoulos-Timogiannakis; Paraskevi Kotrogianni; Despina N. Perrea; Georgios Daskalakis (Tehran University of Medical Sciences, 2018)
Objective: Serum Anti-Müllerian hormone (AMH) has been implicated in the pathogenesis of cardiovascular disease. Its prognostic value in determining the risk of developing preeclampsia remains, to date, unclear. The purpose of the present systematic review is to accumulate current evidence in this field. Materials and methods: We searched Medline (1966-2017), Scopus (2004-2017), Clinicaltrials.gov (2008-2017), EMBASE (1980-2017), LILACS (1986-2017) and Cochrane Central Register of Controlled Trials CENTRAL (1999-2017) databases. Results: Four studies were included in with a total number of 401 women. Among them 146 had preeclampsia while 232 were recruited as normotensive controls. Current data are suggestive of the potential predictive value of serum AMH as its levels seem to be lower among women that develop preeclampsia. One study reported that women with and AMH value below the 10th percentile of the studied population had a 3.3 increased risk of developing preeclampsia (OR 3.3, 95% CI 1.2-8.7, p = 0.01). Conclusion: Taking in mind these findings, future studies are needed in this field to establish optimal cut-off values and evaluate the specificity and sensitivity of this biomarker during the first trimester of pregnancy.